Do the Relocated Residents Differ from Public Residents in Rent Overdue? The Case of DKI Jakarta Public Rental Housing - Yohanna Magdalena Lydia Gultom; Lydia Maulida (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
Housing problems in urban areas are very critical. The increased population growth in DKI Jakarta and the high migration rate from rural to urban areas cause slums. Slums are generated because many households do not have place to live and populate in unauthorized and inappropriate regions. More than 50% of households in DKI Jakarta have yet to own any housing property. In addition, the housing backlog in DKI Jakarta reached 302.319 in 2017. Therefore, housing problems in urban areas are very critical. One way to overcome this issue is to provide a public rental housing program for relocated and general residents with low income—the relocated residents' objective of moving to public rental housing, as they are the victims. The residents lost their livelihoods, the economy was challenging, and it took time to get a job. So, relocated residents in rental public housing are known to have high overdue rent. Previous research about the effectiveness of relocating to public rental accommodations rental public lodgings is minimal. Therefore, public housings create higher rent due in Jakarta. This research's objective is to compare the relocated and general residents in terms of rent overdue in DKI Jakarta public housing. This research analyzes demographic data and public housing rent overdue in 2022. The method used in this research is quantitative with Ordinary Least Square (OLS) regression. The analyzed regression shows that rental public housing status influences rent overdue, and residents with the status relocated residents are more prone to pay the rent overdue, compared to the public residents.